Processo administrativo disciplinar: proposta de fluxo processual no âmbito do Instituto Federal de Educação, Ciência e Tecnologia de Mato Grosso do Sul - Morais, João Batista de (2018)
The Constitution of the Federative Republic of Brazil in force destines Chapter VII of its text to deal with Public Administration in the Country. In the art. 39, caput, it is expected that agents admitted to the Public Service will be subject to a single legal regime. At the federal level, this regime is instituted by Law 8.112 of December 11, 1990. Based on this Law, the Union empowers its effective servants, subjecting them to their general dictates regarding rights and obligations. The legal text establishes a series of duties, obligations and prohibitions for which its transgressions are characterized as administrative illicit. These transgressions, when they occur in theory, should be determined by means of an investigation or disciplinary administrative proceeding (PAD), pursuant to art. 143, of the same normative document. To this end, the authority which is aware of a possible irregularity should establish a commission which will be responsible for conducting the process and producing evidence. Law 8.112 / 90 provides that the process will be carried out through the phases of initiation, administrative inquiry and trial. Through a commission, the investigation and the administrative process will be carried out, without the Law requiring technical or legal training to participate in the process. The disciplinary administrative proceeding commission should conduct its work based on the Law and the principles of law, especially those related to procedural matters, such as due process, legal certainty, among others. From the reading of Law 8.112 / 90 it is possible to realize that it does not explain and establish how each phase of the process should develop, such as the Code of Civil Procedure and the Code of Criminal Procedure. The purpose of this work is to propose the implementation of a process flow and the mapping of the disciplinary administrative process within the scope of the Federal Institute of Education, Science and Technology of Mato Grosso do Sul (IFMS). In this sense, in the search to highlight the importance of a disciplinary administrative process mapped, a questionnaire was applied to the IFMS servers. In addition, an interview was held with the Executive Board of the Rectory, responsible for supporting the disciplinary commissions of this Institute. From the collected results, it can be affirmed that in the institutional scope it is notorious the importance of the existence of a practical manual or of a mapped administrative process. Thus, from the theoretical and practical evidences about the procedural administrative rite and its importance in the scope of the IFMS, this work presents, as a final result, the step-by-step of the PAD, the drawing of the flow chart of this referred process and proposal of its implementation in the institution, as a way of assisting processing committees in the flow that must be followed, pointing out possible risks of nullities that could compromise the validity of said process.